A Family Cluster of Chagas Disease Detected through Selective Screening of Blood Donors: A Case Report and Brief Review - Guillaume Mongeau-Martin; Momar Ndao; Michael Libman; Gilles Delage; Brian J Ward (Canadian Journal of Infectious Diseases and Medical Microbiology)
Chagas disease (CD) is a protozoan infection caused by Trypanosoma cruzi, which is transmitted by triatomine insect vectors in parts of Latin America. In a nonendemic country, such as Canada, spread can still occur via vertical transmission, and infected blood or organ donations. The Canadian Blood Services and Héma-Québec have both implemented selective screening of blood donors for CD based on risk factors. In 2011, Héma-Québec identified two seropositive ‘at-risk’ Chilean siblings who had donated blood in Montreal, Quebec. They were referred to the JD MacLean Centre for Tropical Diseases (Montreal, Quebec) for confirmatory testing (T cruzi excreted-secreted antigen ELISA, polymerase chain reaction and/or radioimmunoprecipitation assay) and follow-up. Screening of the rest of the family revealed two other seropositive family members (the mother and sister). While their geographical history in Chile suggests vectorial transmission, this family cluster of CD raises the possibility of vertical transmission. Congenital infection should always be considered among CD-positive mothers and pregnant women. With blood donor screening, Canadian physicians will increasingly see patients with CD and should know how to manage them appropriately. In addition to the case presentation, the authors review the transmission, screening and clinical management of CD in a nonendemic context.